Joint Effects of Liquidity, Leverage, and Asset Efficiency on Profitability: Evidence from PT Akasha Wira (2014–2024) - Lestari, Reny; Nurmasari, Ifa (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study examines the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on the Net Profit Margin (NPM) of PT Akasha Wira International Tbk from 2014 to 2024. Using a quantitative descriptive approach, secondary data from the company’s audited annual reports were analyzed through descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test) with IBM SPSS 29.0. The findings reveal that CR, DER, and TATO individually have no significant effect on NPM. However, when tested simultaneously, the three variables have a significant influence on NPM. The coefficient of determination (R²) of 0.904 indicates that these variables explain 90.4% of the variation in NPM, while 9.6% is attributed to other factors not included in the model.